Using Multi-Media to Promote Skill Formation in Learning Organisations - Bean, Steve; Winterton, Jonathan (Proceedings of the International Conference on Networked Learning, 1998)
This paper addresses the use of multi-media technology to develop skills in the application of Learning Organisation principles. It offers insights into the practicalities of using a series of forums on the Internet to develop an innovative set of multimedia learning tools which will initially be made available as a CD-ROM product, and will ultimately be delivered through the Internet. The problem of raising skills and competences, especially at intermediate level (craft and supervisory) is the focus of Project DEVELOP (Development, enskilling, learning organization package). The objective is to create a learning organisation package to be used as a framework within enterprises to raise skills and competences. Each module of the package will be an interactive multi-media learning experience, supported by a variety of communications technologies.